Comment: "An Autoregressive Forecast of the World Sugar Future Option Market" - Anderson, O. D. (Journal of Financial and Quantitative Analysis, 1977)
I was interested to read Meyer and Kim [5], where I learned a little about sugar futures, but regret to say that I found the attempted Box-Jenkins analysis singularly lacking in expertise. It is my intention, here, to discuss a few of its most obvious shortcomings. My list will not be exhaustive, but will include just five points.